Práticas de letramento no ensino médio: uma análise sociorretórica do resumo de iniciação científica - Gois, Karla Epiphania Lins de (2021)
This study is based on the socio-rhetorical theory of genres to define and introduce its research object, the abstract of scientific initiation in school. The abstract accompanies a broader genre, the research report, and is published in the proceedings of the Congress of Scientific Initiation (CONIC). It is prepared by students who participate in the Institutional Scholarship Program for Scientific Initiation in high school, of the Institute of Education, Science and Technology of Pernambuco (IFPE). In this setting, the general objective of the research was to analyze how literacy practices are reflected in the organization of the abstract of scientific initiation in high school. First of all, to meet the overall objective, we expose the literacy practices carried out in high school. Then, we place the abstract in relation to the set of genres. Next, we apply the Biasi-Rodrigues (2009) model to identify rhetorical movements and gender conventions used in the abstract of scientific initiation in high school. To discuss literacy practices, we looked at New Literacy Studies (NEL), the concept of academic literacy, based on Lea and Street (2014, 1998). We also cite academic literacy studies in Brazil. From the theory of genres with a socio-rhetorical basis, we highlight the concept of genres, the set of genres, rhetorical education and the academic abstract. We established the corpus with eighty abstracts, prepared by students from Engineering, Agricultural Sciences, Multidisciplinary, Exact and Earth Sciences, Human Sciences and Linguistics, Letters and Arts. With reference to the findings, we identified that the abstracts presented the characteristics of academic abstracts, with the distribution of similar rhetorical units in the six areas, for the presentation of the research, highlighting the main theme and objectives, the presentation of the methodology and the conclusion of the investigation. And, they showed differences in the distribution of subunits between areas, taking into account its own peculiarities. We concluded that the preparation of the abstract involved complex topics, such as literacy, practices, guidelines, models, and context. Finally, we hope that this research can contribute to academic literacy and gender studies in the academic field circulating in secondary education.